2018
DOI: 10.1007/s10661-018-6785-1
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and nitrogen mineralization in Vertisol as mediated by type and placement method of residue

Abstract: Selection of appropriate residue application method is essential for better use of biomass for soil and environmental health improvement. A laboratory incubation experiment was conducted for 75 days to investigate C and N mineralization of residues of soybean (Glycine max L.), chickpea (Cicer arietinum L.), maize (Zea mays L.), and wheat (Triticum aestivum L.) placed on the soil surface and incorporated into the soil. The residue of soybean and chickpea had a greater decomposition rate than that of maize and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…[ 52 ] found that availability of soil N, P and K was considerably decline under control and the treatment that received only chemical fertilizers. This indicates that decreasing N, P and K availability in soil could be a threat to long-term sustainability of crop productivity and soil health [ 53 ] Furthermore, Yang et al [ 54 ] observed that integration of FYM with 75% NPK of SCTR improved the SOC content in surface soil over the initial value or unfertilized plots. A similar trend was observed for P and K availability in soil system, indicating that significantly build up the Olsen P in surface soil with continuous used of FYM (20 Mg ha –1 ) and integration of 75% NPK along with FYM as compared to rest of INM practices.…”
Section: Discussionmentioning
confidence: 99%
“…[ 52 ] found that availability of soil N, P and K was considerably decline under control and the treatment that received only chemical fertilizers. This indicates that decreasing N, P and K availability in soil could be a threat to long-term sustainability of crop productivity and soil health [ 53 ] Furthermore, Yang et al [ 54 ] observed that integration of FYM with 75% NPK of SCTR improved the SOC content in surface soil over the initial value or unfertilized plots. A similar trend was observed for P and K availability in soil system, indicating that significantly build up the Olsen P in surface soil with continuous used of FYM (20 Mg ha –1 ) and integration of 75% NPK along with FYM as compared to rest of INM practices.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the findings of other researchers [14,29,62], decomposition rates were consistently faster in sub-surface-placed than in surface-placed residues as a result of greater soil-residue contact; a more favourable and stable microenvironment, particularly a soil moisture regime; and increased availability of exogenous N for decomposition by microorganisms [65,66]. However, it was reported a higher rate of decomposition of the legume residues when placed on the soil surface, while soil incorporation of residues of wheat and maize resulted in faster decomposition [67]. Our study revealed that 23% and 38% of maize stover was recovered from litter bags over the 150-day wheat-growing cycle in North-West India.…”
Section: Residue Decomposition Kineticsmentioning
confidence: 97%
“…The higher mass loss was observed for the legume mung bean residue, which was mainly due to its high total N content and low C/N ratio compared to the other cereal residues. Residues with greater inherent N decompose more rapidly [62,67,68]. Studies suggested that the availability of nitrogen controls the decomposition of plant residues and particularly cereals with low N content; the soil decomposers are not unable absorb the residue or soil N [69] (Vahdat et al, 2011).…”
Section: Residue Decomposition Kineticsmentioning
confidence: 99%
“…Es un cultivo idóneo debido a que es una planta resistente a la sequía y a las bajas temperaturas (siendo su rango térmico de desarrollo de 5-35 °C) (Aguilar-Raymundo y Vélez-Ruiz, 2013). Además, mejora la calidad del suelo a través de la fijación de nitrógeno (Armenta-Calderón et al, 2016;Jat et al, 2018). Existen dos tipos de garbanzo, el kabuli y desi.…”
Section: Generalidades Del Garbanzounclassified